2010
DOI: 10.1021/cb1001203
|View full text |Cite
|
Sign up to set email alerts
|

ANS Binding Reveals Common Features of Cytotoxic Amyloid Species

Abstract: Oligomeric assemblies formed from a variety of disease-associated peptides and proteins have been strongly associated with toxicity in many neurodegenerative conditions, such as Alzheimer's disease. The precise nature of the toxic agents, however, remains still to be established. We show that prefibrillar aggregates of E22G (arctic) variant of the Abeta(1-42) peptide bind strongly to 1-anilinonaphthalene 8-sulfonate and that changes in this property correlate significantly with changes in its cytotoxicity. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
343
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 347 publications
(367 citation statements)
references
References 37 publications
16
343
3
1
Order By: Relevance
“…Similar behaviour has been observed for -synuclein (Chen et al 2015). (Oma et al, 2005;Bolognesi et al, 2010;Olzscha et al, 2011;Ladiwala et al, 2012). This has also been observed for HypF-N oligomers (Campioni et al, 2010;Bemporad and Chiti, 2012).…”
Section: Resultssupporting
confidence: 62%
“…Similar behaviour has been observed for -synuclein (Chen et al 2015). (Oma et al, 2005;Bolognesi et al, 2010;Olzscha et al, 2011;Ladiwala et al, 2012). This has also been observed for HypF-N oligomers (Campioni et al, 2010;Bemporad and Chiti, 2012).…”
Section: Resultssupporting
confidence: 62%
“…The neurotoxic properties of the Aβ peptide must be linked to the propensity of the peptide to form aggregates that possess certain properties in terms of size and biophysical parameters which are required for cell toxicity. It has previously been suggested that the exposure of hydrophobic surfaces is crucial for the toxicity of protein oligomers and of Aβ aggregates promoting interference of the aggregates with membrane structures [14,15]. Our results strongly support these findings and, in addition, show that p-FTAA can be used to probe early formed prefibrillar species that are linked to cell toxicity.…”
Section: In Vivo and In Vitro Toxicity Directly Correlate With Distinsupporting
confidence: 89%
“…Importantly, we demonstrate that, by binding to α-syn fibrils, Hsp27 significantly decreases hydrophobicity at the fibril surface. This is noteworthy, given the toxicity of aggregates formed from both pathogenic and nonpathogenic proteins correlates with the level of exposed hydrophobicity at the aggregate surface (63). The observed reduction in the relative hydrophobicity of the Hsp27-bound α-syn fibrils suggests that Hsp27 binds to regions of high hydrophobicity and this may decrease the cytotoxicity of the aggregates.…”
Section: Discussionmentioning
confidence: 95%